Development of Dissolution Medium for Rofecoxib in Pharmaceutical Formulations - Prasanna Raju, Y.; Asuntha, G.; Sreenivasa Rao, B.; Ramana Murthy, K.V. (Asian Journal of Chemistry, 2016)
Rofecoxib is a non-steroidal antiinflammatory drug and selective cox-2 inhibitor, used in the treatment of rheumatoid arthritis especially in gastritis and ulcerative conditions. It is chemically designated as 4-[4-(methylsulfonyl) phenyl]-3-phenyl-2-(5H)-furanone. In this present study, dissolution of rofecoxib from two commercial formulations was studied in two different media to evaluate their discriminating power.